A high bile acid environment promotes apoptosis and inhibits migration in pancreatic cancer. Issue 3 (1st March 2022) - Zhu, Shaopu; Yang, Kang; Yang, Shiyi; Zhang, Li; Xiong, Maoming; Zhang, Jiawei; Chen, Bo
ABSTRACT: Bile acids, the main organic solutes in bile, have been established to play an important role at physiological concentrations in gastrointestinal metabolism. However, under pathological conditions, such as cholestatic disease, cholestasis can damage hepatocytes/biliary epithelial cells leading to apoptosis or necrosis. Clinically, pancreatic head cancer usually presents with obstructive jaundice and increased serum bile acid levels, suggesting that pancreatic cancer is intricately correlated with a high bile acid environment in the human body. An increasing body of evidence suggests that bile acids are toxic to normal human and colon cancer cells. Nonetheless, the effect of bile acids on the occurrence and development of pancreatic cancer remains a matter of debate. In the present study, to explore the direct effects of high serum concentrations of bile acids on pancreatic cancer and the possible related mechanisms, human pancreatic cancer (PANC-1) cells were subject to different concentrations of bile acid mixtures to assess cell viability and the migration and invasion ability. Besides, we found that a high bile acid environment could inhibit the proliferation and migration of pancreatic cancer cells through ROS(Reactive oxygen species) induction and the EMT(epithelial-mesenchymal transition) pathway, thereby promoting the apoptosis of pancreatic cancer cells. Abbreviations BAs: Bile Acids; EMT: epithelial-mesenchymal transition; FBS: fatal bovine serum;CCK-8: Cell-Counting-Kit-8; ROS: reactive oxygen species; CA: cholic acid; CDCA: chenodeoxycholic acid; GCDCA: Glycochenodeoxycholic acid; PVDF: Poly vinylidene fluoride Graphical abstract: uf0001